Kepemimpinan Kepala Sekolah dan Kinerja Guru pada Lembaga Pendidikan - Razak, Ahmad; Karnedy, Astari; Budiman, Mutmainnah (Universitas Negeri Makassar, 2024)
Principal leadership is very important in an educational institution. Good principal leadership can make teachers more qualified and responsible. This study aims to determine the effect of principal leadership on teacher performance in educational institutions. Principal leadership is a key factor that can influence the effectiveness of teaching and learning. The method in this writing is literature review. In an effort to understand and summarise previous research, the literature review method was applied to investigate the relationship between Principal leadership style and teacher performance outcomes. Scientific articles, books and other related publications were used as the main data sources. Through a thorough analysis of previous research findings, this study aims to explore key variables that may mediate or moderate the relationship between principal leadership and teacher performance. The results show that principal leadership has a significant influence on teacher performance. The results of this literature study are expected to provide a comprehensive overview of the concept of principal leadership, understand the relevant dimensions of teacher performance, and identify factors that influence the relationship between the two, as well as provide recommendations for improving education management in the institution. This research is expected to be a positive contribution to the development of quality education and effective leadership in the context of educational institutions.